Programmed Cell Death-Ligand-1 expression in Bladder Schistosomal Squamous Cell Carcinoma – There’s room for Immune Checkpoint Blockage? - Madureira, Ana C. (Frontiers in Immunology, 2022)
Schistosoma haematobium, the causative agent of urogenital schistosomiasis, is a carcinogen type 1 since 1994. It is strongly associated with Bladder squamous-cell carcinoma in endemic regions, where it accounts for 53-69% of bladder-carcinoma cases. This histological subtype is associated with chronic inflammation being more aggressive and resistant to conventional chemo and radiotherapy. Immune-Checkpoint-Blockage (ICB) therapies targeting the Programmed-Cell-Death-Protein-1(PD-1)/Programmed-Cell-Death-Ligand-1(PD-L1) axis showed considerable success in treating advanced Bladder urothelial carcinoma. PD-L1 is induced by inflammatory stimuli and expressed in immune and tumor cells. The binding of PD-L1 with PD-1 modulates immune response leading to T-cell exhaustion. PD-L1 presents in several isoforms, and its expression is dynamic. Also, its expression acts as a companion marker for patients' eligibility allowing the identification of positive tumors that are more likely to respond to ICB therapy. The high PD-L1 expression in bladder-urothelial-carcinoma and squamous-cell carcinoma may affect further ICB-therapy application and outcomes. In general, divergent histologies are ineligible for therapy. These treatments are expensive and prone to auto-immune side effects and resistance; biomarkers capable of predicting therapy response are needed. Also, the PD-L1 expression assessment still needs refinement. Studies focused on squamous cell differentiation associated with S. haematobium remain scarce. Furthermore, in low and middle-income regions, where schistosomiasis is endemic, SCC biomarkers are needed. This mini-review provides an overview of the current literature regarding PD-L1 expression in Bladder-Squamous-Cell-Carcinoma and Schistosomiasis. It aims to pinpoint future directions, controversies, challenges, and the importance of PD-L1 as a biomarker for diagnosis, disease aggressiveness, and ICB-therapy prognosis in Bladder-Schistosomal-Squamous-Cell carcinoma.